Crystal structure dependence of red to green light emission by LaOF : Yb3+/Er3+ up-conversion phosphor. (7th December 2018) - Yamamoto, Shin-Ichi; Ohyama, Keito; Ban, Takahiko; Nonaka, Toshihiro
Abstract: Up-conversion (UC) is the conversion of electromagnetic waves from long to short wavelengths. In this study, near-infrared rays (with wavelengths of 980 nm) were upconverted to visible light rays (with wavelengths of 400–750 nm), and the UC luminescence characteristics of lanthanide-doped materials were measured and analyzed. LaOF : Yb 3+ /Er 3+ UC phosphor samples were fabricated by using LaF3 (hexagonal), Yb2 O3 (cubic), and Er2 O3 (cubic) powders. The mole ratio of La : Yb : Er was 1 : 0.01 : 0.01, and LaOF : Yb 3+ /Er 3+ was obtained by baking these materials. The UC emission of yellow to green light was confirmed by the overlapping of green and red light. The emitted light intensity was the highest for the sample baked at 1100 °C for 2 h. Furthermore, x-ray diffraction (XRD) results revealed that the photoluminescence emission intensity increased with increasing integrated intensity of the tetragonal LaOF crystal system.